The EU Towards the Global South During the COVID-19 Pandemic - Kołodziejczyk, Katarzyna (Studies in Politics, Security and Society, 2022)
The subject of the publication is the European Union's (EU) policy towards the countries of the Global South. The book focuses on the EU's external response to COVID-19 intentionally ignoring the topic of pandemic management in relation to Member States and the EU's single market. The publication aims to validate the hypothesis that the European Union has tapped into the pandemic to increase its role in international relations and influence the countries of the Global South. The goal of the publication was to highlight EU actions supporting Global South countries in combating the pandemic regionally dimension. Research methods characteristic of social studies were applied in the publication, including observation, source and statistical methods.